1972
DOI: 10.1042/bj1260211
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the biosynthesis of mitochondrial malate dehydrogenase and the location of its synthesis in the liver cell of the rat

Abstract: A method is described for the isolation of mitochondrial malate dehydrogenase from either the whole tissue homogenate or from the microsomal fraction of rat liver. The procedure involves the treatment of the tissue extract with detergent followed by gel filtration and chromatography on Amberlite CG-50 and DEAE-cellulose. The resulting enzyme was homogeneous by the criterion of gel electrophoresis. Incubation of the microsomal fraction from rat liver under the usual conditions for protein synthesis in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1973
1973
1989
1989

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…Immunological studies on the synthesis of mitochondrial glutamate dehydrogenase [13] and of mitochondrial and cytoplasmic isoenzymes of malate dehydrogenase [25,26] in liver led to the proposal that the synthesis of these enzymes took place on membrane-bound ribosomes. It ~7as further suggested that the microsomal vesicles contained these proteins in an enzymatically active form.…”
Section: Incubation Of a Cell-free Homogenate With [3h]-mentioning
confidence: 99%
“…Immunological studies on the synthesis of mitochondrial glutamate dehydrogenase [13] and of mitochondrial and cytoplasmic isoenzymes of malate dehydrogenase [25,26] in liver led to the proposal that the synthesis of these enzymes took place on membrane-bound ribosomes. It ~7as further suggested that the microsomal vesicles contained these proteins in an enzymatically active form.…”
Section: Incubation Of a Cell-free Homogenate With [3h]-mentioning
confidence: 99%
“…newly synthesized proteins [4], and from the 100 000 g supernatant of the liver homogenate (which contained both extra-and intramitochondrial isozymes). As calculated from enzyme activity determinations before and after immunoprecipitation with the two antisera, the microsomal fraction contains s-MDH as well as m-MDH.…”
Section: Resultsmentioning
confidence: 99%
“…Bingham et at. [4] have already reported synthesis of the mitochondrial MDH in vitro by isolated microsomes. The present data indicate that this newly synthesized enzyme may be considered as the precursor of mitochondrial malate dehydrogenase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations